FORMULASI TABLET EFFERVESCENT DAUN KERSEN (Muntingia calabura L.) DENGAN VARIASI KONSENTRASI EFFERVESCENT MIX - Fitria Susilowati, Anggun Mahirotun Nur Sholikhah, Surya Amal, (Pharmaceutical Journal of Islamic Pharmacy, 2018)
Muntingia calabura L. is one of the type genus Muntingia which grows ever green and always has a lot of benefits but has not been used optimally. This study aims to utilize Muntingia calabura leaves take one form of pharmaceutical preparations namely effervescent tablet. Effervescent tablets are made using dry granulation of the metanol : water extract Muntingia calabura leaves. This study used variations of the concentration of effervescent mix to know the best concentration of the effervescent mix. Method to make it in relative humidity condition (RH) and appropriate temperature. Three of the formula that has made qualified evaluation of granules (time flow, angle of repose, and compresibility) and evaluation of effervescent tablets (weight variation, hardness test, time dissolved, assay test water, and pH level test). The results of analysis, showed that the three all formulas meet the requirement of test characteristics of granule and effervescent tablet. Based on the results of the research can be conclude that the formula with a concentration of 60% (formulation 2) effervescent mix is the best formula. This is due to the formula for concentration of 60% effervescent mix is the concentration that is ideal concentration for effervescent tablets.